J /w Production in d + Au Collisions at ,.;s;;; = 200 GeV at the STAR Experiment - Powell, Christopher (Department of Physics, 2024)
The production of J/'f/; and other quarkonia is of particular interest in relativistic heavy ion collisions, as their yields are supposed to be suppressed in the presence of the hypothesised hot, dense quark gluon plasma. However, there are other in-:,;nedium effects which will also affect the production of J/'f/; (e.g., nuclear absorption, shadowing). To understand the suppression and enhancement of heavy quarkonia in A+A collisions, we must first understand how yields are modified by a nuclear medium where no hot matter is present. Light systems such as p+ A and d+ A are particularly interesting as there are only cold nuclear matter effects present.